PENGARUH TANGGUNG JAWAB SOSIAL DAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR SUB-SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2022 - Situmorang, Renaldi Vandoli; Sidabutar, Rimbun C. D.; Siringoringo, Magdalena J. (JURNAL LENTERA AKUNTANSI, 2024)
This study aims to analyze the effect of corporate social responsibility (CSR) and capital structure on the financial performance of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2022 period. The technique used by the author to complete this study is the multiple linear regression technique and the classical assumption test shows that CSR and capital structure The data analysis technique used in qualitative research is ratio comparison analysis. The research data consists of 65 company financial reports for two years (130 observations). The test results are that CSR and capital structure have a significant effect both partially and simultaneously on the company's financial performance. The Adjusted R² value of 0.492 indicates that the model can explain 49.2% of the variation in financial performance. The F test produces a value of 63.421 with a significance of 0.000 <0.05, while the t test shows that CSR has a significance value of 0.028 <0.05 and DER 0.000 <0.05, which confirms a significant effect.